DC Motor Control Using Laboratory Virtual Instrumentation Engineering Workbench - Bustanul Arifin; Eka Nuryanto Budisusila (Institut Teknologi Dirgantara Adisutjipto, 2020)
Motor has an important role in everyday life. Both are used on a home scale and in the industrial world. To regulate a motor, a good control system is needed. Laboratory Virtual Instrumentation Engineering Workbench abbreviated as LabVIEW is defined as a system engineering software that is used for the needs of testing, measuring, and controlling quickly on accessing hardware in which there is data needed. LabVIEW uses a graphics-based programming language or block diagram while other programming languages use a text base. This study aims to obtain a value of DC motor control. The method used in this research is to assemble the DC motor hardware with the driver followed by connecting it to a myRIO 1900 board controller. By providing variations in frequency and duty cycle, the results of current and voltage and rotation are obtained to determine its effect. The results of this study indicate that by giving a duty cycle of more than 50%, current and voltage are obtained and the motor rotation is linear and forms a horizontal line. The 100 Hz frequency is the best frequency that can produce the highest motor rotation.